Comparison of heart rate deflection and ventilatory threshold during a field cross-country roller-skiing test - Fabre, N.; Passelergue, P.; Bouvard, M.; Perrey, S. (The Journal of Strength and Conditioning Research, 2008)
This study was to assess whether the point of deflection from linearity of heart rate (HRd) could be an accurate predictor of ventilatory threshold (VT2) during a specific cross-country roller-skiing (RS) test. Ten well-trained cross-country skiers performed a maximal and incremental RS test in the field and a standardized maximal and incremental treadmill running (TR) test in the laboratory. Values of oxygen uptake ([latin capital V with dot above]o2) and heart rate (HR) were continuously recorded during all exercises by a portable breath-by-breath gas exchange measurement system and a wireless Polar monitoring system, respectively. The VT2 and HRd points were individually determined by visual analysis during RS. Maximal VO2 (VO2max) and HR were higher (p < 0.05) during TR (67.1 +/- 7.3 ml/min.kg and 196.0 +/- 14.1 bpm, respectively) compared with RS (64.2 +/- 7.3 ml[middle dot]min-1[middle dot]kg-1 and 191.5 +/- 13.1 bpm, respectively). However, a high correlation (r = 0.94, p < 0.01) between TR and RS VO2 max was observed. Paired t-tests showed no significant differences in HR (183.6 +/- 15.1 vs. 185.2 +/- 13.9 bpm) and VO2 (55.5 +/- 7.1 vs. 55.8 +/- 6.1 ml/min.kg) at intensities corresponding to HRd and VT2 during the RS test, respectively; Pearson product-moment correlation coefficients demonstrated significant relationships for HR at the HRd and VT2 points (r = 0.99, p < 0.001) as well as for VO2 (r = 0.95, p < 0.001). Our results indicate that the specific incremental RS test is effective in eliciting HRd in the field for all skiers and is an accurate predictor of VT2. These findings give very interesting practical applications to cross-country coaches and skiers to evaluate and control specific aerobic training loads.